Osteogenic induction of hBMSCs by electrospun scaffolds with dexamethasone release functionality - Martins, Albino (2010)
Electrospun structures were proposed as scaffolds owing to their morphological and structural similarities with the extracellular matrix found in many native tissues. These !brous structures were also proposed as drug release systems by exploiting the direct dependence of the release rate of a drug on the surface area. An osteogenic differentiation factor, dexamethasone (DEX), was incorporated into electrospun polycaprolactone (PCL) nano!bers at different concentrations (5, 10, 15 and 20 wt.% polymer), in a single-step process. The DEX incorporated into the polymeric carrier is in amorphous state, as determined by DSC, and does not in"uence the typical nano!bers morphology. In vitro drug release studies demonstrated that the dexamethasone release was sustained over a period of 15 days. The bioactivity of the released dexamethasone was assessed by cultivating human bone marrow mesenchymal stem cells (hBMSCs) on 15 wt.% DEX-loaded PCL NFMs, under dexamethasone-absent osteogenic differentiation medium formulation. An increased concentration of alkaline phosphatase and deposition of a mineralized matrix was observed. Phenotypic and genotypic expression of osteoblastic-speci!c markers corroborates the osteogenic activity of the loaded growth/differentiation factor. Overall data suggests that the electrospun biodegradable nano!bers can be used as carriers for the sustained release of growth/differentiation factors relevant for bone tissue engineering strategies.